A new insight into the mechanism for cytosolic lipid droplet degradation in senescent leaves. Issue 4 (21st November 2019) - Zhang, Chaoyue; Qu, Yuangang; Lian, Yuji; Chapman, Mingyu; Chapman, Navid; Xin, Jie; Xin, Huawei; Liu, Lin
Abstract : Leaf senescence involves lipid droplet (LD) degradation that produces toxic fatty acids, but little is known about how the toxic metabolites are isolated from the rest of the cellular components. Our ultramicroscopic characterization of cytosolic LD degradation in central vacuole‐absent cells and central vacuole‐containing cells of senescent watermelon leaves demonstrated two degradation pathways: the small vacuole‐associated pathway and the central vacuole‐associated pathway. This provided an insight into the subcellular mechanisms for the isolation of the fatty acids derived from LDs. The central vacuole‐containing cells, including mesophyll cells and vascular parenchyma cells, adopted the central vacuole‐associated pathway, indicated by the presence of LDs in the central vacuole, which is believed to play a crucial role in scavenging toxic metabolites. The central vacuole‐absent intermediary cells, where senescence caused the occurrence of numerous small vacuoles, adopted the small vacuole‐associated pathway, evidenced by the occurrence of LDs in the small vacuoles. The assembly of organelles, including LDs, small vacuoles, mitochondria and peroxisome‐like organelles, occurred in the central vacuole‐absent intermediary cell in response to leaf senescence.